Outcome of ventriculoperitoneal shunt surgery, without prior placement of external ventricular drain in Grades III and IV patients of tubercular meningitis with hydrocephalus: A single institution's experience in the pediatric population and review of literature - Kankane, Vivek Kumar (J Pediatr Neurosci, 2016)
OBJECTIVE: Hydrocephalus is a most common complication of tubercular meningitis (TBM). Relieving hydrocephalus by ventriculoperitoneal shunt (VPS) placement has been considered beneficial in patient in Palur Grades II or III. The role of VPS placement in those of Grades III and IV is controversial, and general tendency is to avoid its use. Some authors have suggested that patient in Grades III and IV should receive a shunt only if their condition improves with a trial placement of external ventricular drain (EVD). However, recent studies suggest that VPS may be undertaken without the trial of an EVD. Our study prospectively evaluates the role of direct VPS placement in patient in Grades III and IV TBM with hydrocephalus (TBMH). MATERIALS AND METHODS: This study was carried out on 50 consecutive pediatric patients of TBMH in Palur Grades III and IV from July 2013 to December 2014 in R.N.T. Medical College and M.B. Hospital, Udaipur, Rajasthan. All patients underwent direct VPS placement, without prior placement of EVD. The outcome was assessed at the end of 3 months using Glasgow Outcome Score. RESULTS: The mean age of patients was 3.25 years (range, 3 months–14 years). Forty (80%) patients were in Grade III, and 10 (20%) were in Grade IV. Good outcome and mortality in Grade IV patients were 30% (3/10) and 10% (1/10), respectively; whereas in Grade III patients, it was 77.5% (31/40) and 0% (0/40), respectively. Twenty-five patients presented with focal neurological deficit at admission, which persisted in only 14 patients at 3 months follow-up. VPS-related complications were observed in 5 (10%) patients. CONCLUSIONS: This study demonstrates that direct VPS surgery could improve the outcome of Grades III and IV TBMH. Despite poor grade at admission, 80% patients in Grade III and 20% patients in Grade IV had a good outcome at 3 months follow-up. Direct VPS placement is a safe and effective option even in a patient in Grades III and IV grade TBMH with a low complication rate.